Exercise-Based Interventions for Blood Pressure Control in Hypertensive Individuals: A Locality-Specific Analysis in Pekauman Village, RT. 15 - Kencana, Amanda Cahaya; Agustini, Meti; Affandi, Ma’ruf; Maulida, Mona; Huda, Muhammad Ainul; Yulida, Yulida (OMNICODE Journal (Omnicompetence Community Developement Journal), 2025)
Hypertension is the disease with the highest mortality rate in the Pekauman area, Banjarmasin City and often does not show early symptoms. Through the implementation of hypertension exercises, a significant decrease in blood pressure was found in hypertensive patients. Through the intervention during 20 minutes of hypertension gymnastics, the results show that hypertension gymnastics can be one of the alternatives to effective and safe hypertension management. The conclusion is hypertension gymnastics can be considered as one of the interventions in managing hypertension in the community.